COMPARISON OF FIBER TO THE HOME NETWORK ATTENUATION USING OPTICAL POWER BUDGET AND LINK POWER BUDGET - Lailatul Qodariyah,; Rachmawati Darma Astuti, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Cileungsi Hijau Residential Area in Bogor Regency has adopted Fiber To The Home (FTTH) technology to meet the increasing demand for high-speed internet access. However, high attenuation remains a technical issue that may affect service quality. This study aims to compare signal attenuation in FTTH networks using two approaches: direct measurement with an Optical Power Meter (OPM) and theoretical estimation using the Link Power Budget (LPB) method. Measurements were conducted at nine Optical Distribution Point (ODP) locations to assess network feasibility based on the EPON standard threshold (-28 dBm). The results showed that eight of the nine ODP points were above the minimum threshold and deemed feasible. Several points, such as ODP B1, B3, C1, and C2, even had better OPM results than LPB estimates, indicating optimal physical installation. However, ODP D1 showed a received power of -28.99 dBm, falling below the standard and declared unfit. This comparison indicates that while LPB is effective as an initial reference, OPM measurements provide more accurate, real-time insights into actual network performance and are essential for early detection of potential disruptions.